Distance-Bounding Protocols: Are You Close Enough? - Dimitrakakis, Christos; A. Mitrokotsa (My University, 2015)
Distance-bounding protocols can offer protection against attacks on access control systems that require users to both verify their credentials and prove their location. However, tradeoffs among accuracy, cost, and privacy are necessary.